2020
DOI: 10.1002/hbm.25135
|View full text |Cite
|
Sign up to set email alerts
|

Strategic white matter injury associated with long‐term information processing speed deficits in mild traumatic brain injury

Abstract: Deficits in information processing speed (IPS) are among the earliest and most prominent cognitive manifestations in mild traumatic brain injury (mTBI). We investigated the impact of white matter fiber location on IPS outcome in an individual basis assessment. A total of 112 acute mild TBI with all CT negative underwent brain DTI and blood sampling for inflammation cytokines within 7 days postinjury and 72 age‐ and sex matched healthy controls with same assessments were enrolled. IPS outcome was assessed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…Similarly, our previous review has demonstrated that depression and anxiety are associated with elevated TNF-α, IL-6, IFN-α, and C-Reactive Protein (CRP) levels [ 9 ]. Overall, the most common systemic cytokines associated with mTBI include IL-6 [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], TNF-α [ 20 , 23 , 24 , 25 ], IL-10 [ 20 , 26 ], IL-1β [ 19 , 20 ], Interleukin-8 (IL-8) [ 20 , 25 ], Interferon Gamma (IFN-γ) [ 20 , 25 ], Interleukin-1RA (IL-1RA) [ 17 , 21 ], Interleukin-4 (IL-4) [ 20 ], and C–C motif chemokine ligand 2 (CCL2) [ 19 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, our previous review has demonstrated that depression and anxiety are associated with elevated TNF-α, IL-6, IFN-α, and C-Reactive Protein (CRP) levels [ 9 ]. Overall, the most common systemic cytokines associated with mTBI include IL-6 [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], TNF-α [ 20 , 23 , 24 , 25 ], IL-10 [ 20 , 26 ], IL-1β [ 19 , 20 ], Interleukin-8 (IL-8) [ 20 , 25 ], Interferon Gamma (IFN-γ) [ 20 , 25 ], Interleukin-1RA (IL-1RA) [ 17 , 21 ], Interleukin-4 (IL-4) [ 20 ], and C–C motif chemokine ligand 2 (CCL2) [ 19 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more and more studies focused on the development of a predictive modal to find out potential diffusion biomarkers and to detect mTBI patients based on machine learning ( Vergara et al, 2017 ). As a recent prediction modal that can identify mTBI patients by developing information processing speed deficits with 96.7% accuracy through the combination of DTI indices and inflammation cytokines levels, the frontal-subcortical neuronal circuits would be a potential diffusion predictor for processing speed performance in mTBI patients ( Bai et al, 2020 ). Compared to these prediction modals, the differential tractography would be an indispensable complementary tool to evaluate axonal loss for individual mTBI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Two-thirds of all concussions occur in children, with 20-40% reporting at least one concussion by the time they reach adolescence. 13 Concussion symptoms include cognitive impairment, prominently problems with attention and processing speed, 47 along with emotional and physical problems, and sleep dysregulation all of which can impact academic performance and overall quality of life. 810 Most children that experience a concussion recover within two weeks of injury, however, 10-30% of children experience symptoms that last longer than 3 months, 1113 with females at greater risk of persistent symptoms.…”
Section: Introductionmentioning
confidence: 99%